ChemInform Abstract: Enantioselective Copper(II)‐Catalyzed Henry Reaction Utilizing Chiral Aziridinyl Alcohols. Issue 16 (April 2015) - Wang, Xiaojuan; Zhao, Wenxian; Li, Gaowei; Wang, Jin; Liu, Guanjun; Liu, Lantao; Zhao, Ruijuan; Wang, Mincan
Abstract A novel type of aziridine based ligands is synthesized and the derivative LIG is successfully applied under optimized conditions for the enantioselective Henry reaction of aromatic aldehydes (I).